Hypothesis of coincidence of shear stresses in the excitation of hair cells - JAROSZEWSKI, Antoni (Archives of Acoustics, 1978)
A new hypothesis of neuromechanical "sharpening" in the cochlea inferred from the available morphological data and from the geometry of the distribution of stereocilia in OHO in relation to the distribution of shear stresses as determined by Tonndorf and by the author on cochlear models is presented.